Violence Against Women During COVID-19 Pandemic - Akel, Marwan (Journal of interpersonal violence, 2022)
The objectives of this study were to correlate several factors - including depression, anxiety, stress and self-esteem levels in both men and women - with the occurrence of domestic violence against women (VAW) during quarantine. This cross-sectional study was carried out in April 2020, in the midst of the COVID-19 pandemic when lockdown procedures were implemented; 86 married couples participated in this study amounting to 172 responses in total. A different questionnaire was set for women and men; the couple filled out their respective questionnaire simultaneously, but privately where one did not see the answers of the other. Inclusion criteria included married couples of all ages that are living together during the lockdown of COVID-19. The results of this study showed that a higher total abuse score was found in 39 females (45.3%; CI: 0.34 - 0.56). Being a Muslim female (Beta =24.80) and females having higher anxiety (Beta=0.97) were significantly associated with higher total abuse scores, whereas higher stress score in female (Beta=-0.61) was significantly associated with lower total abuse scores. In conclusion, this study focuses on VAW as a serious problem while demonstrating its further emergence during quarantine. This study also focused on the effects brought on by lockdown policies, including social and economic factors, and their implications in the increase of VAW during this pandemic.